Do Digital Payments Drive Economic Growth? Evidence from Developing Countries - Dian Putri Lestari; Lukytawati Anggraeni; Salsa Dilla (Indonesian Journal of Fintech, Banking and Financial Services, 2026)
Background: Digital payments have expanded rapidly in recent decades, driving a global shift from cash to cashless transactions and supporting economic efficiency, financial inclusion, and economic recovery. However, their growth remains uneven, with developed countries experiencing stable adoption due to advanced infrastructure, while developing countries face more volatile expansion driven by structural limitations and varying levels of digital readiness.Purpose: This paper aims to examine the impact of digital payment instruments specifically credit cards, debit cards, and e-money on economic growth in developing countries. Additionally, the study aims to assess the role of key macroeconomic factors, including inflation, population growth, and internet penetration, in influencing economic growth. Design/methodology/approach: This study uses panel data from five developing countries Argentina, Brazil, India, Indonesia, and Turkey over the period 2013–2022. Static panel is used and the result indicates that the Fixed Effects Model (FEM) is the most appropriate specification.Finding/Result: Results show that the growth of digital payments enhance economic growth in the developing countries. In detail, credit cards and e-money positively affect economic growth. Additionaly, an increase in population growth and internet penetration reduces economic growth.Conclusion: Empirical results show that credit cards and e-money positively contribute to economic growth. In detail, e-money transactions grow faster than the other digital payment instrument across developing countries, although adoption varies due to differences in digital infrastructure, financial inclusion, and macroeconomic stability.Originality/value (state of the art): This study will contribute to the literature by expanding the determinants of economic growth by considering the rise of digital payments.